The GABA system, a new target for medications against cognitive impairment—Associated with neuroactive steroids - Bäckström, Torbjörn; Turkmen, Sahruh; Das, Roshni; Doverskog, Magnus; Blackburn, Thomas P. (Journal of internal medicine, 2023)
The prevalence of cognitive dysfunction, dementia, and neurodegenerative disorders such as Alzheimer's disease (AD) is increasing in parallel with an aging population. Distinct types of chronic stress are thought to be instrumental in the development of cognitive impairment in central nervous system (CNS) disorders where cognitive impairment is a major unmet medical need. Increased GABAergic tone is a mediator of stress effects but is also a result of other factors in CNS disorders. Positive GABA‐A receptor modulating stress and sex steroids (steroid‐PAMs) such as allopregnanolone (ALLO) and medroxyprogesterone acetate can provoke impaired cognition. As such, ALLO impairs memory and learning in both animals and humans. In transgenic AD animal studies, continuous exposure to ALLO at physiological levels impairs cognition and increases degenerative AD pathology, whereas intermittent ALLO injections enhance cognition, indicating pleiotropic functions of ALLO. We have shown that GABA‐A receptor modulating steroid antagonists (GAMSAs) can block the acute negative cognitive impairment of ALLO on memory in animal studies and in patients with cognitive impairment due to hepatic encephalopathy. Here we describe disorders affected by steroid‐PAMs and opportunities to treat these adverse effects of steroid‐PAMs with novel GAMSAs.